Formulation Design and Characterization of Lamivudine Controlled Release Matrix Tablets (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: To design and characterize oral controlled release matrix tablets of lamivudine to improve efficacy and patient compliance. Materials and Methods: Lamivudine matrix tablets were prepared by wet granulation method using various proportions of hydrophilic polymers such as sodium carboxymethylcellulose (Na CMC), hydroxypropyl methylcellulose (HPMC), Eudragit-L155, and xanthan gum alone or in combination with hydrophobic polymer ethyl cellulose (EC). In-vitro release studies were performed using USP Type II dissolution apparatus 900 ml of pH - 6.8 phosphate buffer at 100 rpm. Drug release kinetics was analyzed using zero-order, first-order, Higuchi and Hixon equation. No chemical interaction between drug and the polymer was seen as confirmed by Fourier transform infrared studies. Results and Discussion: All the formulations showed good results which were compliance with pharmacopeial standards. Formulations X2, X3, X4, X5, X7, X9, X12, and X14 containing a combination of two polymers, i.e., xanthan gum, combine with EC, Na CMC, HPMC, and Eudragit-L155 in the different ratios shows zero-order kinetic of release with 80-97% of drug released. But in the presence of Na CMC in the formulation X4, X9, and X14, the drug released in 12 h was in the range of 75-85% and shows zero-order kinetics. Mathematical analysis of the release kinetics indicated that the nature of drug release from the matrix tablets was dependent on drug diffusion and therefore followed non-Fickian or anomalous release. The formulation X4 containing xanthan gum with Na CMC gave more sustaining action, i.e., 79.16% in 12 h. Conclusion: Based on the in-vitro drug release study, it can be concluded that among the prepared formulations, X4 is the optimized formulation and can overcome the demerits of conventional lamivudine tablet.